Salivary 8-hydroxy-2′-deoxyguanosine levels in patients with oral cancer: a systematic review and meta-analysis - Alarcón-Sánchez, Mario Alberto; Escoto-Vasquez, Lilibeth-Stephania; Heboyan, Artak (BMC cancer, 2024)
DNA is an important target for oxidative attack and its modification may increase the risk of mutagenesis. The aim of this study was to evaluate and compare salivary levels of the oxidative stress biomarker 8-hydroxy-2'-deoxyguanosine (8-OHdG) in patients with oral cancer (OC) compared to the control group by a comprehensive search of the available literature. The present systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines and was registered in Open Science Framework (OSF): https://doi.org/10.17605/OSF.IO/X3YMR. Four electronic databases were used to identify studies for this systematic review: PubMed, Scopus, ScienceDirect, and Web of Science from January 15, 2005, to April 15, 2021. The Joanna Briggs Institute (JBI) tool was used to assess article quality. Of the 166 articles identified, 130 articles were excluded on the basis of title and abstract screening (duplicates, reviews, etc.). Thirty-six articles were evaluated at full text and 7 articles met the inclusion criteria. Of these, only 5 studies had compatible data for quantitative analysis. An increase in salivary 8-OHdG levels was found in patients with OC compared to healthy subjects, but without statistical significance. 8-OHdG: SMD = 2,72 (95%CI= -0.25-5.70); *p = 0.07. This systematic review and meta-analysis suggests a clear trend of increased 8-OHdG levels in saliva of OC patients compared to the control group. However, further studies are required to clarify and understand the altered levels of this oxidative stress marker.